Infrastructure Regulation : A Review of International Instruments and Compliance Mechanisms - Alexandrov, Stanimir A. (World Bank, Washington, DC, 2013)
The paper reviews first the most formal such instruments, such as bilateral and multilateral treaties, that include commitments regarding regulatory processes and/or outcomes. Next, it will consider less formal instruments, such as institutional guidelines and model rules, that promote principles for regulatory good practices. Finally, it will consider the different mechanisms available to promote compliance with these norms using both binding and non-binding devices. Two tables summarizing the assessments of these instruments and compliance mechanisms are appended at the conclusion of the report.Furthermore, this paper undertakes to review the international instruments that incorporate standards for domestic regulatory good practices or move toward creating international regulatory regimes, and the mechanisms that promote or secure compliance with those good practices and regimes.